PENILAIAN PELANGGAN MENURUT PERSEPSI KEPUASAN DAN KEPENTINGAN PADA FASILITAS RUANG PUBLIK STASIUN KERTAPATI DAN TANJUNG KARANG - Asrizal Muslim; Bambang Utoyo S (Jurnal Tekno Global, 2020)
Kertapati (KPT) and Tanjung Karang(TNK) central stations serve as passangers’ arrival, departure points and goods handling facilities. Those facilities should be supported by public service facilities the needs of the users. One method the measure the needs of the users is servedon user’s survey on. On user’s survey on perception on needs. The research measures the indeks of the user’s perception on needs and satisfaction at two stasions, analysis the gap between satisfaction, needs and ranks the priority of satisfaction and need. The research carry out based on a qualitative descriptive research method in which a Servqual Analysis was utilities measure the users’perspective subsequanley an IPA Analysis are utilited to measure the priority important. Parameters were based on minimum standard level (SPM No.48 Tahun 2015) from Ministry of Transportation that were Safety, Security, Reliability, Comfort, Accessibility and Equality. The respondents was choosen based on accidental sampling whose already experienced and journey with trains. The results are beneficial to get insight about the sustainable improvement as well as to determaine the priority of improvement needed. Result from the stations are good service with several variables being the priority of improvement. Access to disability with gap of -1.13 for KPT and -1.02 for TNK. The stairs go up and down to the train with gap of -1.12 for KPT. The public toilets with gap of -0.93 for KPT and -0.98 for TNK. Disabled facilities with gap of -1.09 for TNK. Toilet for disabled people with a gap of -1.07 for TNK.Keywords: Perception, Satisfaction, Importance, Servqual, IPA